Best Answer

-(x-5)

When you take the integers out right behind the "-" is a 1. so when you expand it will equal -x+5

Q: What is -x plus 5 factorised?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5 - x^2 = (the square root of 5 minus x)(the square root of 5 plus x)

(x + 4)(x + 1)

5x2 + 20 = 5*(x2 + 4) which cannot be factorised further.

6x³ +12x + 18 = 6(x + 1)(x² - x + 3)

It is 3(2y+5) when factorised

Related questions

5 - x^2 = (the square root of 5 minus x)(the square root of 5 plus x)

(x + 4)(x + 1)

x - 5 is in its simplest form.

5x2 + 20 = 5*(x2 + 4) which cannot be factorised further.

x2 + 4x + 3 = (x + 1)(x + 3)

6x³ +12x + 18 = 6(x + 1)(x² - x + 3)

x^2-x+1 cannot be factorised

It is 3(2y+5) when factorised

3x2+26x+16 When factorised: (3x+2)(x+8)

(-5 +/- sqrt(25 -24)) /2 = (-5 +/- 1)/2 = -2.5 +/- 0.5 = -2 or -3 Factorised (x + 3)(x + 2) which confirms answers above.

x2-9x+18 = (x-3)(x-6) when factorised

x2-6x+9 = (x-3)(x-3) when factorised.